Involvement of Retinoblastoma Protein and HBP1 in Histone H1(0) Gene Expression - Lemercier, Claudie (American Society for Microbiology, 2000)
The histone H1(0)-encoding gene is expressed in vertebrates in differentiating cells during the arrest of proliferation. In the H1(0) promoter, a specific regulatory element, which we named the H4 box, exhibits features which implicate a role in mediating H1(0) gene expression in response to both differentiation and cell cycle control signals. For instance, within the linker histone gene family, the H4 box is found only in the promoters of differentiation-associated subtypes, suggesting that it is specifically involved in differentiation-dependent expression of these genes. In addition, an element nearly identical to the H4 box is conserved in the promoters of histone H4-encoding genes and is known to be involved in their cell cycle-dependent expression. The transcription factors interacting with the H1(0) H4 box were therefore expected to link differentiation-dependent expression of H1(0) to the cell cycle control machinery. The aim of this work was to identify such transcription factors and to obtain information concerning the regulatory pathway involved. Interestingly, our cloning strategy led to the isolation of a retinoblastoma protein (RB) partner known as HBP1. HBP1, a high-mobility group box transcription factor, interacted specifically with the H1(0) H4 box and moreover was expressed in a differentiation-dependent manner. We also showed that the HBP1-encoding gene is able to produce different forms of HBP1. Finally, we demonstrated that both HBP1 and RB were involved in the activation of H1(0) gene expression. We therefore propose that HBP1 mediates a link between the cell cycle control machinery and cell differentiation signals. Through modulating the expression of specific chromatin-associated proteins such as histone H1(0), HBP1 plays a vital role in chromatin remodeling events during the arrest of cell proliferation in differentiating cells.